The health professional experience of using antipsychotic medication for dementia in care homes: A study using grounded theory and focussing on inappropriate prescribing. Issue 5 (19th July 2018) - Almutairi, Saleh; Masters, Kate; Donyai, Parastou
Accessible summary: What is known on the subject: People with dementia can experience symptoms that upset them and upset the people who care for them To cope, care homes sometimes use strong medicines called antipsychotics but these can make people with dementia become more ill We do not know just why doctors and nurses caring for people with dementia still use these strong medicines more than they need to What the paper adds to existing knowledge: Giving antipsychotics can make it easier to care for residents within busy care homes, so people tend to see and remember the benefits of antipsychotics The harm of antipsychotics is noticed less, meaning carers will use them again, in a "vicious circle" What are the implications for practice: If these medicines worked before it does not make them the right choice again It might help to show carers very clearly the harms from using these medicines, to stress the dangers Abstract: Introduction: Treating the behavioural and psychological symptoms of dementia with antipsychotics can cause detrimental side‐effects but their use in care homes remains problematic with the views of professionals not fully explored. Aim/question: To develop an in‐depth explanatory model about inappropriate prescribing of antipsychotics in dementia within care homes. Methods: Twenty‐eight participants from eight different professional groups with a role in shaping treatment decisions in dementia care were recruited and interviewed. The audio‐recorded interviews were transcribed and analyzed using constructivist grounded theory. Results: When patients with dementia present with behavioural and psychological symptoms, the prescribing of antipsychotics allows the multitude of work in a care home to be managed; the effectiveness of antipsychotics is more perceptible than their side‐effects. This perceived usefulness strengthens beliefs that these medications ought to be prescribed again in future situations, generating a self‐fulfilling prophecy. Discussion: Our findings may partly explain why the launch of the national dementia strategy in England has been found not to have reduced antipsychotic prescribing in care homes. Implications for practice: Positive perceptions based on past experiences with antipsychotics should be challenged through future interventions that tackle inappropriate prescribing, for example using behaviour change techniques to better highlight adverse consequences of prescribing.